2016
DOI: 10.1055/s-0036-1586120
|View full text |Cite
|
Sign up to set email alerts
|

Does Ventilatory Time Retain Its Validity in Predicting Neurodevelopmental Outcome at Two Years of Age in High-Risk Congenital Diaphragmatic Hernia Survivors?

Abstract: To evaluate if in high-risk non-extracorporeal membrane oxygenation (ECMO)-treated congenital diaphragmatic hernia (CDH) survivors, ventilatory time (VT) is correlated to and can be used as clinical marker of neurodevelopmental delay at 2 years of age. Cohort study was conducted between 2008 and 2012. Mental, motor, and language development were assessed by the Bayley Scales of Infant and Toddler Development III. The correlation between VT and neurodevelopmental outcome (NDO) was analyzed using Pearson's test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Finally, 90 studies were included in this review, reporting on 24,930 children with CDH (Table ). This included 83 case series 15,17−21,33‐110 , four cohort studies, 16,111‐113 and three randomized controlled trials 7,114,115 . Nine studies reported only on isolated CDH cases 7,21,52,76,85,91,104,105,109 and in four studies a differentiation was made between isolated and nonisolated cases 39,51,81,94 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 90 studies were included in this review, reporting on 24,930 children with CDH (Table ). This included 83 case series 15,17−21,33‐110 , four cohort studies, 16,111‐113 and three randomized controlled trials 7,114,115 . Nine studies reported only on isolated CDH cases 7,21,52,76,85,91,104,105,109 and in four studies a differentiation was made between isolated and nonisolated cases 39,51,81,94 …”
Section: Resultsmentioning
confidence: 99%
“…Cognitive deficits were reported in 22 studies. 7,16,17,19,33,37,38,[40][41][42]47,63,74,75,80,83,88,94,109,[111][112][113] In total, 10% (7%-15%) of CDH children scored abnormal. The majority of these studies used BSID and if only BSID results were analyzed, 14% (8%-20%) of children scoring abnormally.…”
Section: Cognitionmentioning
confidence: 99%
See 3 more Smart Citations